Trait‐related responses to habitat fragmentation in Amazonian bats. Issue 5 (16th July 2015) - Farneda, Fábio Z.; Rocha, Ricardo; López‐Baucells, Adrià; Groenenberg, Milou; Silva, Inês; Palmeirim, Jorge M.; Bobrowiec, Paulo E. D.; Meyer, Christoph F. J.
Summary: Understanding how interspecific variation in functional traits influences species' capacity to persist in fragments and use patches in fragmented landscapes is fundamental for the creation of effective conservation plans. This study uses phylogenetic comparative methods to investigate which functional traits of bat species are correlated with their vulnerability to fragmentation in a tropical landscape with low fragment–matrix contrast. Bats were captured over two years in eight forest fragments, nine control sites in continuous forest, and in the secondary forest matrix at the Biological Dynamics of Forest Fragments Project, Central Amazon, Brazil. We tested the hypothesis that there is a significant relationship between species functional traits, environmental gradients (continuous forest and fragment interiors, edges and matrix) and patterns of species distribution using phylogenetic generalized least squares (PGLS) models, as well as a combination of RLQ and fourth‐corner analyses. Mobility, body mass, wing morphology, and trophic level were the most important traits linked to fragmentation sensitivity based on the PGLS analysis, while body mass and trophic level emerged as the best predictors in the fourth‐corner analysis. These last two traits were correlated with the loss of continuous forest characteristics, such as high‐stature trees and forest cover. Many animalivorous bat species rarely persist in small fragments (<100 ha) and in the secondary forest matrix, reflecting strong effects of trait‐mediated environmental filters that selectively benefit the smaller and phytophagous species. Synthesis and applications . Functional traits of species and environmental variables jointly predict local variation in patterns of bat occupancy and abundance in fragmented tropical landscapes. To minimize local extinctions, we recommend increasing habitat availability and enhancing structural and functional connectivity at the landscape scale through the creation, restoration and maintenance of corridors and stepping stones. These measures should be coupled with improving matrix quality by promoting secondary forest regeneration and persistence to effectively reduce fragment–matrix contrast. Abstract : Functional traits of species and environmental variables jointly predict local variation in patterns of bat occupancy and abundance in fragmented tropical landscapes. To minimize local extinctions, we recommend increasing habitat availability and enhancing structural and functional connectivity at the landscape scale through the creation, restoration and maintenance of corridors and stepping stones. These measures should be coupled with improving matrix quality by promoting secondary forest regeneration and persistence to effectively reduce fragment–matrix contrast.